A comparative protein profile of accessory glands of virgin and mated Leucinodes orbonalis males. (26th November 2020) - Saraswathi, Saraswathi; Bodampalli Sarvesh, Chaitra; Kiran, Tannavi; Ravindran, Mamtha; Ramachandra, Sowrabha; Rao, Karthik V.; Doddamane, Manjulakumari
Abstract: Male accessory gland (MAG) secretory proteins affect female reproductive physiology and behaviour when they are delivered to the female at the time of mating along with sperm. In our study, proteomic approaches were used to identify MAG proteins of Leucinodes orbonalis, a monophagous and destructive pest of brinjal. A set of 117 and 186 MAG spots were observed in virgin and mated males, respectively, using two‐dimensional gel electrophoresis (2D‐GE). Among the identified spots, 49 are unique to the virgin, whereas 118 are unique to mated MAGs, with 68 spots found to be common. The differentially expressed MAG proteins, 14 are up‐regulated, and 16 are down‐regulated in virgin after mating. We used matrix‐assisted laser desorption ionization (MALDI)–mass spectrometry (MS) to identify the 13 unique proteins in the MAG of virgin L. orbonalis and analysed the data of the Swiss‐Prot database using the Mascot search engine. The proteins were identified as proteolysis regulators, lipid transporters, olfactory proteins, metabolism‐related proteins, DNA‐binding proteins, and hexamerins. This is the first report on the gel‐based protein analysis of L. orbonalis MAGs. Abstract : Leucinode orbonalis male accessory gland (MAG) protein profile by 2D‐GE revealed a total of 117 and 186 proteins in virgin and mated MAGs, respectively. Among the identified proteins, 49 are unique to virgin and 118 to mated MAGs, with 68 being common. Differentially expressed proteins following mating were 14 up‐regulated and 16 down‐regulated. The 13 unique spots sequenced from the virgin MAGs are involved in various reproduction‐related functions.